Motivasi Kerja dan Produktivitas Kerja Guru pada SMP NW Jerua Kabupaten Lombok Timur - Hadi, Samsul (ARZUSIN, 2024)
Organization is a place for a group of individuals to work together to achieve predetermined goals. Human Resource Management (HRM) is an important aspect in the success of the organization, especially in increasing competitiveness and productivity. Teachers' work motivation is instrumental in creating enthusiasm and passion, which impacts productivity. Leaders play a key role by providing encouragement, responsibility and opportunities for employees to actively contribute, including in decision-making. However, employee motivation can be influenced by various factors, such as education level and economic conditions, so the right approach needs to be applied to increase work passion. The purpose of this study was to analyze teachers' work motivation and the impact of work motivation on work productivity at NW Jerua Junior High School. This research method uses a qualitative approach with a case study research type. Data collection through observation, interviews, and documentation. Data analysis using data reduction (Data Reduction), data presentation (Data Display) and conclusiondrawing and verification (Conclusion Drawing and Verification). This research was conducted at SMP NW Jerua in East Lombok Regency with a focus on analyzing the work motivation of teachers and its impact on productivity. The results showed that work motivation at SMP NW Jerua is quite good, teachers get support and encouragement from the teachers.